Robert T. Anderson and Terry Giles. The Keepers: An Introduction to the History and Culture of the Samaritans. Peabody, MA: Hendrickson Publishers, 2002. 300 pp. - Pummer, Reinhard (AJS review, 2004)
The Keepers is a concise and informative introduction to the history and religion of the Samaritans, that branch of the Israelite-Jewish religion that has endured from antiquity to the present among a tiny minority in Palestine and Israel. The book is written in an engaging style that will appeal to a public that would not read specialized works on the subject. At the same time, the information contained in the work is reliable and the authors are careful in their discussions of unsolved (and often unsolvable) issues. In an epilogue, Anderson and Giles underline that there remains a “host of unanswered questions about the history and culture of the Samaritan community” and that this book is “only a beginning” (p. 145).